Gender representations in children's media and their influence. Issue 2 (2014) - ,
Abstract : Purpose – The purpose of this paper is to draw attention to the significant underrepresentation of females and stereotypical portrayals of both females and males that still exist in different kinds of media children are exposed to, as well as to various negative influences these may have on children's development. In addition, this paper intends to show up the potential positive effects of non‐sexist gender representations in these media.Design/methodology/approach – The paper reviews studies that have been conducted on various kinds of media, in order to gain and provide a representative overview of gender portrayals and of possible influences they might have on children.Findings – Women are underrepresented in children's literature, television programs, as well as computer‐related software. Traditional portrayals of females are also still the norm in these media that children are daily faced with. Alarming trends regarding the representations of males have also been found. The negative influence of sexist representations on children has been shown by numerous studies, as has been the potential of positively affecting children's development by exposing them to non‐traditional gender representations.Originality/value – Awareness of how highly present sexism still is in media for children and of the ways in which it may inhibit children's development is seen as a crucial step toward change. Change in this field is needed if we want to ensure a better, more equal future for our world.